2022
DOI: 10.32865/fire202273291
|View full text |Cite
|
Sign up to set email alerts
|

Cambodian Teachers' Perceptions of Online Teaching: During and Beyond the COVID-19 Pandemic

Abstract: This limited topical life history study aims to gain insights into COVID-19’s impacts on teaching at upper secondary schools through Cambodian teachers’ perceptions of online teaching. It presents teachers’ current challenges and needs as well as future impacts on their teaching practices. Online semi-structured interviews were conducted to collect data from 29 subject teachers and their school directors. This study concluded that the COVID-19 pandemic reduced the quality of teaching and learning due to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition, teachers who participated in the study utilized online meeting platforms like Zoom, Teamlink, plus applications and tools such as WhatsApp, e-mail, Web 2.0 tools, virtual classrooms, social media, and PowerPoint. Likewise, studies conducted in Sweden by Berghdal and Nouri (2020) and in Cambodia by Soeung and Chim (2022) also found that teachers use applications such as Zoom, Google Meet, Microsoft Teams, and Google Classroom in emergency remote teaching processes. Similarly, in a study conducted by Ayaz (2021) with teachers and students, it was found that Web applications, Zoom, Skype, WhatsApp, YouTube, and virtual classrooms were used in the process.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, teachers who participated in the study utilized online meeting platforms like Zoom, Teamlink, plus applications and tools such as WhatsApp, e-mail, Web 2.0 tools, virtual classrooms, social media, and PowerPoint. Likewise, studies conducted in Sweden by Berghdal and Nouri (2020) and in Cambodia by Soeung and Chim (2022) also found that teachers use applications such as Zoom, Google Meet, Microsoft Teams, and Google Classroom in emergency remote teaching processes. Similarly, in a study conducted by Ayaz (2021) with teachers and students, it was found that Web applications, Zoom, Skype, WhatsApp, YouTube, and virtual classrooms were used in the process.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the study concluded that teachers believe that distance education could be used part-time as an alternative practice for students with transportation problems or in urgent situations and in presenting theoretical information or as a technology-supported method. Also, Bozkurt (2020), Maloney and Joshua Kim (2020), and Soeung and Chim (2022) underline the expectations regarding teachers' blended teaching. Cahapay (2020) also suggests that blended learning can be used in education in post-pandemic periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews were conducted in the local language, Khmer, and lasted approximately 30 minutes (Appendix A). Online interviews provided informants with a more confidential environment to express their viewpoints, compared to face-to-face interviews conducted in a classroom or on a school campus (Soeung & Chim, 2022).…”
Section: Qualitative Datamentioning
confidence: 99%
“…Due to the outbreak of COVID-19, there are new challenges for teaching and learning in the Cambodian education (Soeung & Chim, 2022). Online learning and blended learning have been implemented in Cambodian education to fight against the negative impact of social distancing required to combat the COVID-19 pandemic.…”
mentioning
confidence: 99%